IMPLEMENTASI E-KINERJA DALAM MENINGKATKAN AKUNTABILITAS PEGAWAI DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN CIAMIS: - - Gina Mardiana; Uci Triyanti Dewi; Irfan Nursetiawan (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
The implementation of the e-Performance system is an innovative step in managing employee performance in the government environment. This study aims to evaluate the implementation of e-Performance in improving employee accountability at the Personnel and Human Resources Development Agency of Ciamis Regency. This study uses a qualitative descriptive approach, data were collected through interviews and observations of four informants consisting of junior expert and first expert apparatus resource analysts, using interview guidelines, notebooks and voice recorders. The results of the study indicate that the implementation of e-Performance carried out in the work environment of the BKPSDM of Ciamis Regency has had a positive impact in improving the efficiency, transparency and accountability of employee performance, although its success is influenced by the educational background and competency of employees. The main challenge faced is the lack of understanding of technological developments among human resources apparatus. This study concludes that understanding and implementing the use of e-Performance is an important step in achieving organizational goals and improving overall performance in the work environment of the BKPSDM of Ciamis Regency. The BKPSDM of Ciamis Regency should continue to improve employee technological competence through regular training and technical assistance to optimize the use of e-Performance. Keywords: E-Performance, Implementation, Employee Accountability, BKPSDM Ciamis Regency.